A review on the application of Bacillus as probiotics in aquaculture. Issue 87 (April 2019) - Kuebutornye, Felix K.A.; Abarike, Emmanuel Delwin; Lu, Yishan
Abstract: Probiotics use in aquaculture has gained attention as microbial candidates to maintain the health and the well-being of many aquaculture animals. Among the many microbial candidates, probiotic Bacillus has sporulation capacity that makes them survive harsh environmental conditions, are non-pathogenic and non-toxic when fed to fish, and can produce antimicrobial substances making them more suitable candidates compared to other probiotics. In this review, we discussed the necessity of using the probiotic Bacillus in sustainable aquaculture as a good alternative to improve feed utilization, stress response, immune response and disease resistance, maintenance of tissue integrity, and as well improvement of water quality for sustainable aquaculture. Therefore the findings of current researches about the effects of Bacillus application to improve the culture of aquatic animals for future research and development of Bacillus application in aquaculture have been summarised.